Maternal Age, Parity, And Hemoglobin Levels Associated With The Incidence Of Low Birth Weight - Ni Putu Arik Armawati; Sri Rahayu; Ni Made Dwi Mahayati (International Journal of Health Engineering and Technology, 2026)
Low Birth Weight (LBW) is a health problem that contributes to high neonatal mortality rates. Factors thought to influence the incidence of LBW include maternal age, parity, and hemoglobin levels. This study aims to determine the relationship between maternal age, parity, and hemoglobin levels with the incidence of LBW at the Jimbaran 1 Sub-Health Center in 2025. This study used an analytical design with a cross-sectional approach, with a sample of 205 respondents selected using a simple random sampling technique. The data used were secondary data from a maternal cohort and analyzed using the Spearman Rank test. The results showed that most respondents were at a non-risk age (83.4%), had a non-risk parity (63.4%), and did not experience anemia (64.4%). The incidence of LBW was 13.7%. The analysis showed a significant relationship between maternal age and the incidence of LBW (p=0.017) and hemoglobin levels with the incidence of LBW (p=0.003). Meanwhile, parity did not have a significant relationship with the incidence of LBW (p=0.682). The conclusion of this study is that maternal age and hemoglobin levels are associated with the incidence of low birth weight (LBW). It is recommended that healthcare professionals increase efforts to prevent anemia and educate about healthy reproductive ages to reduce the incidence of low birth weight (LBW).